Elucidating the role of extracellular polymeric substances (EPS) in dewaterability of fecal sludge from onsite sanitation systems, and changes during anaerobic storage. (15th August 2022) - Sam, Stanley B.; Ward, Barbara J.; Niederdorfer, Robert; Morgenroth, Eberhard; Strande, Linda
Highlights: Fecal sludge can be degraded during anaerobic storage using an inoculum. Extracted EPS has a significant effect on fecal sludge dewatering time. EPS concentrations are lower in fecal sludge than wastewater sludges. Fecal sludge has higher humic-like fraction of EPS compared to wastewater sludges. Time in anaerobic storage is not a predictor of fecal sludge dewaterability. Abstract: As the importance of fecal sludge management (FSM) is increasingly being realized, the need for adequately designed and functioning fecal sludge (FS) treatment plants is also increasing. Research to fill this gap is only emerging and dewatering is a key challenge for developing sustainable treatment solutions. This study evaluated the effect of extracellular polymeric substances (EPS) on dewaterability of FS, and how EPS and dewaterability change during anaerobic storage (as a proxy for time in onsite containment). EPS was extracted from FS and activated sludge using Na2 CO3 and sonication and added to sludge samples to determine the effect on dewaterability. The results confirmed that an increase in EPS had a direct impact of decreasing FS dewaterability (as capillary suction time). In this context, we evaluated FS degradation during anaerobic storage, the effect of anaerobic storage time on EPS, EPS fractions and particle size distribution, and the effect of variations in these factors on FS dewaterability. Variations in EPS, EPS fraction and particle size distribution during anaerobic storage were less than expected and average VS reduction of 20% was recorded over 7 weeks. Although anaerobic digestion was verified (biogas production), the results indicate that kinetics of degradation of FS is different from wastewater sludges. Comparatively, EPS fractions in FS were 70 – 75% lower and with higher fractions of humic-like substances than wastewater sludges. Although EPS significantly affects FS dewaterability, anaerobic storage time is not a predictor of dewaterability. Graphical abstract: Image, graphical abstract